ANALISIS ASUHAN KEPERAWATAN DENGANINTERVENSI TERAPI DIAPHRAGMATIC BREATHINGEXERCISE DAN PURSED LIP BREATHING UNTUKMENINGKATKAN STATUS PERNAPASAN PADA PASIENPENYAKIT PARU OBSTRUKTIF KRONIS (PPOK) DI IGD RSBHAYANGKARA TK.I R. SAID SUKANTO - Alfiyatul Hasanah, (2023)
The lung condition known as COPD flow is characterized by shortness of air and ongoing breathing problems caused by obstructions in the airways or abnormalities in the alveolar lung tissue caused by noxious substances or gases. The leading cause of death worldwide is a non-communicable disease called COPD. One of the symptoms of COPD that people may experience is shortness of breath. Pursed lip breathing is a loss treatment that can be used to improve breathing patterns. Controlling the rate and depth of thickness will help slow expiration, prevent collapse of the small airways, and promote relaxation. Diaphragmatic Breathing Exercise Therapy (diaphragmatic breathing exercises) can also increase oxygen saturation and ventilation efficiency in oxygen by increasing the amount of oxygen in the bloodstream. The results of the analysis show that banning patients with breathing problems, such as poor breathing patterns in COPD patients, diaphragmatic breathing exercises, and lip breathing can help lower the dyspnea scale. To overcome complaints of shortness of breath in patients, especially in patients with a diagnosis of COPD, it is hoped that new therapies such as breathing exercises and lip breathing can be carried out by inclusive workers as independent interventions in the field. Keywords : COPD, dyspnea, diaphragmatic breathing exercise, pursed lip breathing